Pendampingan Model Bisnis dan Pemasaran Digital pada Pengrajin Wuwung Hias Desa Kalongan Bantul - Djaelani Susanto; Subarjo Subarjo; Busthanul Arifin (Parta: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aims to strengthen business capacity and expand market access for decorative wuwung craftsmen in Kalongan Village, Bantul Regency, through business model mentoring and digital marketing assistance. The main problems faced by the craftsmen include limited generational regeneration, dependence on middlemen, weak product branding, and low utilization of digital technology in marketing. The program was implemented through preparation, training, and hands-on mentoring stages, focusing on knowledge transfer of traditional wuwung craftsmanship from senior artisans to younger participants and practical training in digital marketing using social media and online marketplaces. A participatory and practice-based approach was applied to ensure direct implementation of acquired skills. The results indicate an improvement in participants’ knowledge and skills in both wuwung production and digital promotion. Participants successfully created business social media accounts and began uploading promotional content for their products. This program contributes to preserving local cultural heritage while enhancing the economic independence of craftsmen through technology-based capacity building. Sustainable impact requires continuous mentoring and strengthened marketing networks.